Effect of nickel oxide thin films on photoconversion efficiency in zinc oxide dye-sensitized solar cells - Surat Futemvong (2018)
ZnO dye-sensitized solar cells (ZnO DSSCs) with different thickness of NiO thin films coated in photo-electrode and counter-electrode were investigated. NiO thin films were prepared by thermal evaporation of NiO onto FTO glass substrate. The films were characterized by FE-SEM. For the photo-electrode, NiO thin films were coated on ZnO with 0.2, 0.6, 1.1 and 2.2 mg to form a barrier layer. For the counter-electrode, NiO thin films were coated on FTO glass with 5.4, 10.8, 16.2 and 21.6 mg in order to increase a surface-to-volume ratio. The photoconversion efficiency of ZnO DSSCs was measured under illumination of stimulated sunlight obtained from solar simulator with the radiant power of 100 mW/cm2. It was found that ZnO DSSCs coated with 0.6 mg NiO in photo-electrode and 10.8 mg in counter-electrode exhibited the highest photoconversion efficiency of 1.00% and 0.92%, respectively. The enhancement of photoconversion efficiency with NiO coating maybe explained by decreasing of charge recombination in photo-electrode and increasing of active surface area in counter-electrode. © (2011) Trans Tech Publications.